FIRST REPORT OF BIG ONION FLOWER MOLD CAUSED BY Aspergillus niger on Allium cepa L. in SRI LANKA (Proceedings of the International Conference on Agriculture, 2018)
Big onion is a main cash crop grown in Sri Lanka. However, the crop is highly susceptible to diseases: anthracnose, purple blotch, bulb rot and black mold. Although black mold disease symptoms are associated with the onion bulb, black moldy growth on onion flowers has been observed to be spreading in Sri Lanka during the last decade resulting in the reduction of quantity and quality of onion seeds.  Hence, this study was conducted with the objective of isolation and identification of causal agents of the onion flower mold. Big onion flower samples with mold symptoms were collected during Maha season 2016/17 from the major onion growing areas of Anuradhapura and Matale districts.  Four organisms were isolated from onion flower:  Aspergillus, Penicillium, Collectrotichum and Altenaria. Out of the four, Aspergillus dominated.  Hence, Aspergillus sp. isolated from onion flowers was compared with the causative agent of black mold of onion bulbs. Koch’s postulation studies of flower and bulb inoculation with respective Aspergillus isolates resulted the same black color molds in the flower and bulb Inoculation of other fungal isolates did not show the black old symptoms in flower and bulb. PCR amplification with ITS1/ITS4 universal primers confirmed the isolated Aspergillus from flower as well as bulb are to be A. niger. Results confirmed that the onion flower black mould disease is caused by A. niger: the causal organism of onion bulb black mold as well.
Keywords: Aspergillus; Black mold; Flower; Onion; Sri Lanka